2021
DOI: 10.1111/jpi.12765
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces proliferation and promotes apoptosis of bladder cancer cells by suppressing O‐GlcNAcylation of cyclin‐dependent‐like kinase 5

Abstract: Melatonin helps to maintain circadian rhythm, exerts anticancer activity, and plays key roles in regulation of glucose homeostasis and energy metabolism. Glycosylation, a form of metabolic flux from glucose or other monosaccharides, is a common post‐translational modification. Dysregulated glycosylation, particularly O‐GlcNAcylation, is often a biomarker of cancer cells. In this study, elevated O‐GlcNAc level in bladder cancer was inhibited by melatonin treatment. Melatonin treatment inhibited proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…However, melatonin (7) has been found to inhibit the proliferation of bladder cancer cells and induces apoptosis via blocking O-GlcNAcylation of CDK5 (Figure 1). 73 CDK1/2/5 kinase activity is significant for interferon γ (IFNG)-mediated tumor immune evasion. Use of the CDK1/2/5 inhibitor dinaciclib (1) induced apoptosis of tumor cells and stimulated CD8+ T cell-dependent antitumor immunity in pancreatic cancer.…”
Section: Cdk5 Functions In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, melatonin (7) has been found to inhibit the proliferation of bladder cancer cells and induces apoptosis via blocking O-GlcNAcylation of CDK5 (Figure 1). 73 CDK1/2/5 kinase activity is significant for interferon γ (IFNG)-mediated tumor immune evasion. Use of the CDK1/2/5 inhibitor dinaciclib (1) induced apoptosis of tumor cells and stimulated CD8+ T cell-dependent antitumor immunity in pancreatic cancer.…”
Section: Cdk5 Functions In Cancermentioning
confidence: 99%
“…It is anticipated that these advancements will facilitate the clinical translation of these inhibitors in the future. Inhibition of CDK5 has been shown to mediate the cell death of tumor-initiating cells (TICs), 148 promote the differentiation of ductal progenitors into β-cell, 149 promote the differentiation of osteoblasts and fracture healing, 150 reduce the proliferation of cancer cells and promote apoptosis, 73 and others. Despite the potential benefits of CDK5-selective inhibitors, progress in their development has been hindered at the primary stage.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For instance, in gastric cancer cells, melatonin induced apoptosis by downregulating the mouse double minute 2 homolog (MDM2) [ 28 ]. It also induced apoptosis by suppressing o-GlcNAcylation of cyclin-dependent-like kinase 5 (CDK5) in bladder cancer cells [ 29 ]. In a mouse ovarian tumor xenograft model, melatonin prompted apoptosis by stabilizing Bim via Sp1-mediated tumor domain-containing protein 1 (OTUD1) upregulation [ 30 ].…”
Section: Anticancer Effect Of Melatoninmentioning
confidence: 99%
“…Melatonin has previously been shown to inhibit the growth of BC (Reiter et al 2017 ). Wu et al ( 2021 ) further revealed the anti-prostate cancer mechanism of melatonin: Melatonin inhibits O -GlcNAcylation of cyclin-dependent kinase 5 (CDK5) at Thr246, thus promoting its degradation, and inhibiting the tumor-promoting effect of CDK5 on BC cells.…”
Section: O -Glcnac and Cancermentioning
confidence: 99%